Recent advances in the application of hydrophilic interaction chromatography for the analysis of biological matrices. (November 2015) - Hendrickx, Stijn; Adams, Erwin; Cabooter, Deirdre
Hydrophilic interaction chromatography (HILIC) is being increasingly used for the analysis of hydrophilic compounds in biological matrices. The complexity of biological samples demands adequate sample preparation procedures, specifically adjusted for HILIC analyses. Currently, most bioanalytical assays are performed on bare silica and ZIC-HILIC columns. Trends in HILIC for bioanalysis include smaller particle sizes and miniaturization of the analytical column. For complex biological samples, multidimensional techniques can separate and identify more compounds than 1D separations. The high volatility of the mobile phase, the added separation power and high sensitivity make MS the detection method of choice for bioanalysis using HILIC, although other detectors such as evaporative light scattering detection, charged aerosol detection and nuclear magnetic resonance have been reported.